Desinformação, fake news e a eleição presidencial de 2022 : análises dos casos e formas de combate nas eleições - Gomes, Matheus Arruda (2023)
The present study aims to analyze disinformation and verify whether or not there was influence of Fake News in the presidential elections of 2022, analyzing the extent to which there is freedom of expression on the internet in the digital age, bringing as a possibility the protection given by the Superior Electoral Court in the prevention of the dissemination of disinformation through fake news, especially with regard to the virtual environment, in order to avoid the spread of fake news and hate speech in the context of the Brazilian elections. Thus, fake news and hate speech, which are constantly evolving as an instrument harmful to democracy and the exercise of universal suffrage before the Superior Electoral Court, use instruments and platforms to verify this news in a timely manner. Thus, it is questionable whether the spread of disinformation and fake news in the 45 days prior to the presidential elections has an impact on the outcome of the polls, given that the goal of an election is to be as transparent and fair as possible, fostering the construction of a true representative democracy. The research method used was the deductive one, since the study was based on bibliographic research and, for the survey of the problem, the qualitative approach was adopted. With the presentation of the theme it is expected to contribute to the enrichment of the study of the theme, providing reference for consultation for future research.